THE INFLUENCE OF COMPUTER TECHNOLOGY DEVELOPMENT ON SOCIAL BEHAVIOR - Rahmat Idhami; Robet Silaban; Andri Saputra; Taufa Fadly; Muhammad Amin (RADJA PUBLIKA, 2025)
The development of computer technology has brought significant changes to various aspects of people's lives, including social behavior. Computers integrated with the internet network not only function as data processing tools but also as the main medium for communication, social interaction, and the formation of new social relations. This study aims to analyze the influence of the development of computer technology on people's social behavior through a literature study approach. The research method used is a literature review of relevant scientific articles, which discuss the relationship between the use of computer technology and changes in social behavior. The results of the study indicate that the development of computer technology has positive impacts, such as ease of access to information, expansion of social networks, and increased digital literacy in society. However, negative impacts were also found, including reduced intensity of face-to-face social interactions, the emergence of digital dependency, and changes in social values ​​and communication norms in society. These changes indicate that computer technology plays a significant role in influencing the social dynamics of modern society. Therefore, it is necessary to utilize computer technology wisely so that the resulting social benefits can be optimized without ignoring the social and cultural values ​​that apply in community life.